Edukasi Hukum Tentang Kenakalan Remaja Tanpa Memandang Jenis Kelamin: (Konsekuensi Hukum Bagi Laki Laki dan Perempuan) - Ilvani Ervanda Putri; Adinda Sofia Nasution (Institut Nalanda, 2026)
Juvenile delinquency continues to represent a complex social and legal problem affecting adolescents across different social backgrounds and genders. Despite the principle of equality before the law, public perceptions and institutional responses toward delinquent behavior frequently differ between male and female offenders. This study aims to examine juvenile delinquency from a gender-neutral legal perspective and to analyze the legal consequences imposed on male and female adolescents who commit unlawful acts. The research employs a normative juridical method through the examination of statutory regulations, legal doctrines, and relevant academic literature concerning juvenile justice systems. The analysis focuses on how legal frameworks regulate responsibility, sanctions, and rehabilitation mechanisms for juvenile offenders without discrimination. The findings indicate that existing legal provisions generally emphasize equal legal treatment for all juveniles regardless of gender, particularly through principles of child protection, restorative justice, and rehabilitation. However, in practice, certain disparities still emerge due to cultural assumptions, social stigma, and differing expectations toward boys and girls. These factors may influence law enforcement attitudes and the implementation of rehabilitative measures. Therefore, strengthening a consistent gender-neutral approach within the juvenile justice system is essential to ensure fairness, legal certainty, and the protection of children's rights while promoting effective prevention.